Los juegos recreativos para mejorar la atención de los niños de primer año de educación general básica, de la escuela Filomena mora de Carrión de la ciudad de Loja en el periodo 2019 – 2020. - Macas Cango, Sandra Paulina (2020)
This research is aimed at how recreational games improve the attention of children at the Filomena Mora de Carrión school; With the general objective of improving attention through recreational games for children in the First year of Basic General Education, the approach is mixed, the methods used were: scientific, descriptive, inductive, and statistical; For data collection, the observation and interview technique applied to the classroom teacher was used, and the instrument used was the Guide for the evaluation of care for children between 5 and 6 years of age, the investigated population comprises 27 children and 1 teacher. The results allow us to determine that 74% of the students had attention problems, being in a deficient and very deficient range. To improve this problem, the alternative proposal called "Playing with attention, I learn with emotion" was designed and applied, based on recreational games, where the results obtained show that 89% of the children significantly improved their attention, concluding that teachers and educational institutions must implement this methodological tool within their pedagogical plans and develop them in classrooms, to support to the improvement of cognitive processes in infants.